2014
DOI: 10.1152/physiolgenomics.00179.2013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biological pathways associated with a 1.37 Mbp genomic region protective of hypertension in Dahl S rats

Abstract: The goal of the present study was to narrow a region of chromosome 13 to only several genes and then apply unbiased statistical approaches to identify molecular networks and biological pathways relevant to blood-pressure salt sensitivity in Dahl salt-sensitive (SS) rats. The analysis of 13 overlapping subcongenic strains identified a 1.37 Mbp region on chromosome 13 that influenced the mean arterial blood pressure by at least 25 mmHg in SS rats fed a high-salt diet. DNA sequencing and analysis filled genomic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…These three genes harbor four non-synonymous variants and demonstrate a consistent protective effect on PP in the FBPP. ASTN1 and its two upstream genes RFWD2 and PAPPA2 have been shown to be strongly expressed in the renal outer medulla and show protective effects on HTN in Dahl S rats [43,44], consistent with what we observed with humans in this study. This effect may be mediated through pathways that affect BP via renal transcellular Na and K electrochemical gradients and tubular Na transport, mitochondrial TCA cycle and cell energetics, and circadian rhythms [43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These three genes harbor four non-synonymous variants and demonstrate a consistent protective effect on PP in the FBPP. ASTN1 and its two upstream genes RFWD2 and PAPPA2 have been shown to be strongly expressed in the renal outer medulla and show protective effects on HTN in Dahl S rats [43,44], consistent with what we observed with humans in this study. This effect may be mediated through pathways that affect BP via renal transcellular Na and K electrochemical gradients and tubular Na transport, mitochondrial TCA cycle and cell energetics, and circadian rhythms [43].…”
Section: Discussionsupporting
confidence: 92%
“…ASTN1 and its two upstream genes RFWD2 and PAPPA2 have been shown to be strongly expressed in the renal outer medulla and show protective effects on HTN in Dahl S rats [43,44], consistent with what we observed with humans in this study. This effect may be mediated through pathways that affect BP via renal transcellular Na and K electrochemical gradients and tubular Na transport, mitochondrial TCA cycle and cell energetics, and circadian rhythms [43]. For humans, we used the GTEx database [34] to search for the expression domains of the four genes: ASTN1 is mainly expressed in the brain; and, SEC16B is highly expressed in the kidney and liver ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…33 More complex statistical analyses to evaluate the impact of expression changes on molecular networks and alteration of disease phenotype are also warranted. 34 …”
Section: Working Group’s Recommendations On Scientific Questions and mentioning
confidence: 99%
“…Additionally, the application of RNA‐Seq in HTN mouse models for transcriptome profiling revealed novel potential mechanisms involved in the pathophysiology of HTN and its complications. Cowley et al . identified genes and biological pathways associated with a protective effect on Dahl salt‐sensitive rats.…”
Section: Breakthrough Discoveries With Rna‐seqmentioning
confidence: 99%
“…Additionally, the application of RNA-Seq in HTN mouse models for transcriptome profiling revealed novel potential mechanisms involved in the pathophysiology of HTN and its complications. Cowley et al 63 identified genes and biological pathways associated with a protective effect on Dahl saltsensitive rats. Tain et al 64 identified genes of importance for programmed HTN, through transcriptome characterization of the offspring of pregnant mouse models under suboptimal conditions (high fructose and dexamethasone administration).…”
Section: Breakthrough Discoveries With Rna-seqmentioning
confidence: 99%